Konten Kurikulum Pendidikan Islam - Azwir Salam (Departement of Mathematics Education, 2024)
The curriculum is a guideline for implementing education and learning in order to achieve educational goals and learning objectives. Objectives can be achieved if the relevant curriculum contains lesson content that is relevant to the intended objectives. This article discusses what content the Islamic education curriculum should contain. The content of the Islamic education curriculum in question is guided by the Quran and Sunnah as its main principles. Apart from that, the opinions of leading Islamic education experts or thinkers will be discussed regarding the content of the Islamic education curriculum. This research is research in the nature of a literature study which aims to find a foundation for building a theoretical basis, framework of thinking and research hypotheses. The way to collect data in this research is to use various kinds of literature, both books and relevant journal articles. The results of this research show that: The main contents that can be used as the basic framework or content of the Islamic education curriculum are: (1) Essential knowledge in the formation of the Muslim personality, which includes faith, sharia and morals; (2) Knowledge about the sources of religion and Islamic teachings, consisting of the Quran and Hadith; (3) Arabic as a scientific tool in understanding teaching sources; (4) Sciences related to humanity and society with its various branches